Maids or mentors? The effects of live-in foreign domestic workers on children's educational achievement in Hong Kong. Issue 1 (2nd January 2016) - Tang, Sam Hak Kan; Yung, Linda Chor Wing
Abstract : This paper studies the effects of live-in foreign domestic workers (FDWs) on school children's educational outcomes using samples from two population censuses and a survey data set. The evidence consistently points to Filipino FDWs improving the educational outcomes of school children by decreasing their probability of late schooling or increasing their scores of core academic subjects. English-speaking ability and maturity are shown to be the most important assets of the Filipino FDW in improving children's educational outcomes. These findings suggest that FDWs provide an important childrearing service.